The Shift toward Fusha (Classical Arabic Language) Reconstruction of the Concept - Shareef Klaib Alshraideh, Safa; A. Alhourani, Haya (Dirasat: Human and Social Sciences, 2022)
This research aims to re-formulate the concept of conversion to classical Arabic, in light of the challenges it faces in the era of globalization, and the failure of attempts to impose fusha in the street and in schools and universities, By trying to uncover pragmatic methods, that succeed in bringing life back to Standard Arabic in different sectors, But with a less perfect outlook, more closer to the user’s need, it suggests various ways to achieve this. In this context, the research seeks to answer questions such as: Does speaking “ fusha” represent a priority issue in light of the rampant weakness in public education? can the project of “ shifting to fusha” in the street and in the classroom succeed? What is the purpose of shifting to fusha? How does Fusha contribute to preserving and strengthening Arab culture? Who should undertake this task? What are the roles of the different parties to achieve the required goal?